Timing of emergency medical services activations for falls - Elizabeth Sheridan, MPH, MACPR; Jessica M. Wiseman, MPH; Carmen E. Quatman, MD, PhD (Archives of Gerontology and Geriatrics Plus)
Objective: Falls are a major challenge to public health, particularly among older adults. Understanding factors that influence fall risk is pivotal in the prevention of falls and fall-related injuries. This study evaluated the timing of emergency medical service (EMS) activations for falls and transport patterns for adults age ≥65. Methods: A patient care report system at a single fire-based emergency medical service agency in a suburban, Midwest city was retrospectively reviewed. Type of call (lift assist/fall), time of injury (time, day, and month), and demographics (sex, age) were collected for residents age ≥65 who activated 9–1–1 for a lift assist or fall. Results: 1169 calls met inclusion criteria. Mornings and afternoons were the time of day associated with falls (33 % and 36 % of EMS activations, respectively, vs. 21 % and 10 % for evenings and nights, respectively; p = 0.002) while day of the week and month were not associated with falls or lift assists. More males requested lift assists than females (256 vs. 238) and more females called for falls than males (408 vs. 267; p < 0.001). Falls were more likely to be associated with transport to the hospital than lift assists (78% vs. 7 %). Female sex was associated with increased risk for transport to the hospital (60 % of females vs. 40 % of males; p < 0.001). Conclusions: Mornings and afternoons were associated with increased risk for falls and sex (female) with increased risk for transport to the hospital.